2018
DOI: 10.1519/jsc.0000000000002194
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Monitoring in Basketball: Applications, Player Responses, and Practical Recommendations

Abstract: Berkelmans, DM, Dalbo, VJ, Kean, CO, Milanović, Z, Stojanović, E, Stojiljković, N, and Scanlan, AT. Heart rate monitoring in basketball: applications, player responses, and practical recommendations. J Strength Cond Res 32(8): 2383-2399, 2018-The aims of this review were to collate the existing literature encompassing heart rate (HR) monitoring in basketball to (a) identify the applications of HR measurement; (b) report HR responses in male and female players during training and game-play; (c) evaluate use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 56 publications
0
40
0
1
Order By: Relevance
“…The large number of original and review articles on HR monitoring published in recent decades documents the high interest in exercise and sport science (Task Force, 1996 ; Achten and Jeukendrup, 2003 ; Aubert et al, 2003 ; Carter et al, 2003 ; Sandercock et al, 2005 ; Hottenrott et al, 2006 ; Borresen and Lambert, 2008 ; Bosquet et al, 2008 ; Alexandre et al, 2012 ; Daanen et al, 2012 ; Plews et al, 2013 ; Stanley et al, 2013 ; Buchheit, 2014 ; Hettinga et al, 2014 ; Bellenger et al, 2016 ; Kingsley and Figueroa, 2016 ; Berkelmans et al, 2017 ). The growing popularity of HR measures among practitioners (Akenhead and Nassis, 2016 ; Thorpe et al, 2017 ), combined with the increasing number of commercial products and software for HR recording and analysis (Naranjo et al, 2015 ; Flatt and Esco, 2016 ; Perrotta et al, 2017 ; Plews et al, 2017b ) further highlights the practical significance of this research field.…”
Section: Hr Monitoring In Athletesmentioning
confidence: 99%
See 2 more Smart Citations
“…The large number of original and review articles on HR monitoring published in recent decades documents the high interest in exercise and sport science (Task Force, 1996 ; Achten and Jeukendrup, 2003 ; Aubert et al, 2003 ; Carter et al, 2003 ; Sandercock et al, 2005 ; Hottenrott et al, 2006 ; Borresen and Lambert, 2008 ; Bosquet et al, 2008 ; Alexandre et al, 2012 ; Daanen et al, 2012 ; Plews et al, 2013 ; Stanley et al, 2013 ; Buchheit, 2014 ; Hettinga et al, 2014 ; Bellenger et al, 2016 ; Kingsley and Figueroa, 2016 ; Berkelmans et al, 2017 ). The growing popularity of HR measures among practitioners (Akenhead and Nassis, 2016 ; Thorpe et al, 2017 ), combined with the increasing number of commercial products and software for HR recording and analysis (Naranjo et al, 2015 ; Flatt and Esco, 2016 ; Perrotta et al, 2017 ; Plews et al, 2017b ) further highlights the practical significance of this research field.…”
Section: Hr Monitoring In Athletesmentioning
confidence: 99%
“…Over a wide range of endurance exercise intensities, exercise HR (HRex) is linearly related to oxygen uptake and energy expenditure during continuous work and is therefore commonly used to monitor and prescribe exercise intensity and training load (Achten and Jeukendrup, 2003 ; Borresen and Lambert, 2009 ; Alexandre et al, 2012 ; Berkelmans et al, 2017 ). Furthermore, exercise HR has been traditionally evaluated under submaximal (HRex) and maximal efforts (HRmax) using incremental tests to assess cardiovascular fitness (Achten and Jeukendrup, 2003 ; Buchheit, 2014 ).…”
Section: Hr Monitoring In Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal changes in physical capacities of basketball players from T2 to T3; however, this may be due to the analysis of HR responses in absolute terms (bpm) and not in percentage (%) to the maximal HR. Indeed, a prolonged period of training at high physiological loading during the different seasonal phases might have affected the maximal HR [35]. Furthermore, it has been reported that HR showed some limitations as indicator of aerobic performance capacity [36].…”
Section: Plos Onementioning
confidence: 99%
“…HR and oxygen consumption are used for predicting maximal oxygen consumption during tests. HR is a useful parameter to monitor exercise intensity, to assess fatigue status, and to quantify internal training loads in intermittent team sports, e.g., running basketball (Berkelmans et al, 2018).…”
Section: Introductionmentioning
confidence: 99%